2011
DOI: 10.5624/isd.2011.41.4.151
|View full text |Cite
|
Sign up to set email alerts
|

Description of mandibular bone quality based on measurements of cortical thickness using Mental Index of male and female patients between 40-60 years old

Abstract: Purpose : The purpose of this study was to obtain the description of the mandibular bone quality of male and female patients between 40-60 years old and their differences based on mandibular cortical bone thickness measured using Mental Index (MI). Materials and Methods : Forty digital panoramic radiographs, which consisted of twenty male and twenty female patients, 40-60 years old, were observed. Mandibular cortical bone thickness was measured using MI on both sides of the mandible. The average MI score of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
1
15
0
6
Order By: Relevance
“…The structural parameters such as thickness, number and separation of the trabecular bone were found to be related to osteoporotic subjects and the reported ranges of values for identifying a low BMD or osteoporosis were almost similar to the linguistic terms associated with each attribute in this study. 34 Furthermore, several studies 6,7,21,35,36 suggested the cutoff threshold of cortical width as the most appropriate threshold for referral for bone densitometry and it is also similar to the ranges of values obtained from MF in this study.…”
Section: Discussionsupporting
confidence: 71%
“…The structural parameters such as thickness, number and separation of the trabecular bone were found to be related to osteoporotic subjects and the reported ranges of values for identifying a low BMD or osteoporosis were almost similar to the linguistic terms associated with each attribute in this study. 34 Furthermore, several studies 6,7,21,35,36 suggested the cutoff threshold of cortical width as the most appropriate threshold for referral for bone densitometry and it is also similar to the ranges of values obtained from MF in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Estrogen mencegah osteoporosis dengan menghambat efek stimulasi sitokin pada osteoklas. 20 Estrogen berperan dalam menurunkan sekresi sitokin proinflamasi oleh monosit serta sumsum tulang seperti IL-1, TNF-α, dan IL-6. Sitokin proinflamasi ini berguna untuk menstimulasi perekrutan dan aktivitas osteoklas melalui peningkatan RANKL dan menurunkan ekspresi OPG.…”
Section: Pembahasanunclassified
“…15 Penelitian Ledgerton tahun 1997 menyatakan bahwa Mental Index mengalami penurunan berdasarkan umur dan lebih rendah pada wanita dibandingkan pria dan lebih rendah pada pasien dengan osteoporosis dibandingkan dengan wanita yang sehat. 16 Ledgerton et al (1999) 20 Indeks mandibula seperti jumlah kehilangan gigi, resorpsi tulang alveolar, penebalan lamina dura, ketebalan kortikal pada mandibula dan morfologi pada Mandibular Inferior Cortex (MIC) menjadi berguna dalam screening untuk mengetahui penurunan densitas mineral tulang. Pemeriksaan radiografi pada mandibula dapat merupakan proses yang efektif dalam mendiagnosis osteoporosis secara dini.…”
unclassified
“…[4] Although changes in the bone mass and calcium metabolism are evident in the premenopausal period, menopause marks the beginning of bone loss that continues until the end of life and is a main cause of osteoporotic fractures in elderly women. [1,5] Apart from the hormonal risk factor, there are other risk factors for osteoporosis, particularly: Family history, insufficient calcium intake, lack of moderate physical exercise, toxic habits such as smoking and excessive consumption of alcohol or medications, especially glucocorticoids. [1,5] As a consequence of osteoporosis, pathological fractures occur, which is a serious health and economic problem; hence, the early diagnosis of this pathology is important.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a systemic bone disease that is characterized by generalized decrease of the bone mass and deterioration of bone microarchitecture. [1][2][3] It is one of the most common disorders of the elderly and is estimated that 75 million people in Europe, Japan, and the United States are affected. [2] It is a significant health problem for middle-aged women, coinciding with menopause.…”
Section: Introductionmentioning
confidence: 99%